The Influence of Teacher Teaching Skills And Literacy Culture on The Results of Learning Islamic Religious Education Students - Asep Maman Sahuri (AT-TURATS, 2020)
This study aims to find out how much influence the teaching skills of teachers and literacy culture on the learning outcomes of Islamic Education. The benefit of this research, it is expected that an educator continues to learn by following various trainings so that the learning process runs well and the increasing student learning outcomes in Islamic Education subjects. The method used in this research is descriptive quantitative by using survey approach with descriptive data presentation analysis. The population of this research is grade VIII students of SMP Negeri in Bayah Subdistrict. The sample in this study amounted to 80 respondents from 402 populations. Sample collection uses random sampling techniques, data collection using questionnaires and tests. Data analysis uses two-track variance analysis. Before conducting the analysis, first performed a validity test with Product Moment Correlation and reliability using Alpha Cronbach against research instruments. Validity and reliability test results show that all research instruments are valid and reliable research variables. The results showed that there was no significant influence of teacher teaching skills (X1)on learning outcomes (Y) and there was no significant influence of literacy culture (X2)on learning outcomes (Y). However, when the study was conducted correlation jointly between teacher teaching skills (X1)and literacy culture (X2)to the learning outcomes of Islamic Education students (Y) in SMP Negeri in Bayah subdistrict there was a significant influence.